ASME 2016 Internal Combustion Engine Division Fall Technical Conference 2016
DOI: 10.1115/icef2016-9349
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Add-On Hydrous Ethanol Dual Fuel Systems to Reduce NOx Emissions From Diesel Engines

Abstract: Aftermarket dual-fuel injection systems using a variety of different fumigants have been proposed as alternatives to expensive after-treatment to control NOX emissions from legacy diesel engines. However, our previous work has shown that available add-on systems using hydrous ethanol as the fumigant achieve only minor benefits in emissions without recalibration of the diesel fuel injection strategy. This study experimentally re-evaluates a novel aftermarket dual-fuel port fuel injection (PFI) system used in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Overall, soot emissions decreased drastically, reaching near 90% reduction from CDC levels at high FEF. This result is somewhat contrary to our earlier hydrous ethanol PFI work [1][2][3] which showed that soot emissions remained high even at significant FEF. With reformed ethanol, as FEF increased, engine combustion was more premixed with significantly less directly injected diesel.…”
Section: Engine Performance and Emissionscontrasting
confidence: 99%
See 4 more Smart Citations
“…Overall, soot emissions decreased drastically, reaching near 90% reduction from CDC levels at high FEF. This result is somewhat contrary to our earlier hydrous ethanol PFI work [1][2][3] which showed that soot emissions remained high even at significant FEF. With reformed ethanol, as FEF increased, engine combustion was more premixed with significantly less directly injected diesel.…”
Section: Engine Performance and Emissionscontrasting
confidence: 99%
“…However, the high load condition experienced only a minor increase before decreasing, indicative of the high CE seen during this condition, providing further evidence that ISR operation is most beneficial at high loads. Unlike our previous work with hydrous ethanol [1][2][3], no unburned ethanol was present at engine outlet conditions. Instead, THC emissions consisted mainly of methane, depicted in Figure 6 and smaller amounts of acetaldehyde and formaldehyde.…”
Section: Engine Performance and Emissionsmentioning
confidence: 86%
See 3 more Smart Citations